Diabetes Distress among Individuals Living with Diabetes in Semarang, Indonesia: A Cross-sectional Study - Nadya Yumna; Niken Safitri Dyan Kusumaningrum (Holistic Nursing and Health Science, 2026)
Individuals with diabetes often experience psychological challenges that may affect their health outcomes, one of which is diabetes distress. If unrecognised and unmanaged, it can impair coping abilities and self-management behaviours. This study aimed to describe the diabetes distress level among individuals with diabetes in a primary health care setting. A descriptive cross-sectional study was conducted involving individuals with diabetes residing in the working area of a public health centre in Semarang, Central Java, Indonesia. Participants were recruited consecutively, and data were collected using the Indonesian version of the Diabetes Distress Scale (DDS). Descriptive analysis was performed, and results were presented as frequencies and percentages. A total of 105 individuals participated, with a mean age of 58.5 ± 10.0 years. Overall, all participants reported slight or no diabetes distress. Specifically, none of the participants reported difficulties in physician-related distress or interpersonal distress domains. However, a small proportion experienced moderate or severe distress, particularly in the emotional burden domain (14.3%), while only 2.9% reported moderate or severe distress related to regimen adherence. Diabetes distress did not vary according to demographic or clinical characteristics. These findings indicate a generally low level of diabetes distress in this primary health care population; nevertheless, emotional burden remains a concern for some individuals. This study underscores the importance of maintaining mental health and adopting a holistic, person-centred approach to diabetes care that integrates psychosocial screening into routine primary care services. Future research with larger and more diverse samples and longitudinal designs is recommended.